New records of Gerromorpha and Nepomorpha (Insecta: Hemiptera: Heteroptera) from South America - Moreira, Felipe; Rodrigues, Higor; Barbosa, Julianna; Reduciendo Klementová, Barbora; Svitok, Marek (Biodiversity Data Journal, 2016)
Aquatic and semiaquatic Heteroptera occur on all continents except Antarctica and occupy a wide variety of habitats, including lentic and lotic water bodies, perennial or temporary. In the Neotropical Region, there is a lack of knowledge concerning the geographical distribution of most represented species, which can only be solved by the collection of specimens in under-studied areas and publication of new records and lists of species. New records are presented for eleven species of Gerromorpha and ten Nepomorpha, including first records from Venezuela ( Brachymetra lata , Limnogonus hyalinus , Rhagovelia evidis , Tenagobia peruana , Limnocoris burmeisteri , L. fittkaui fittkaui , Placomerus micans , and Martarega gonostyla ), the Venezuelan State of Bolívar ( Cylindrostethus palmaris , R. elegans , R. tenuipes , and Ambrysus stali ), the Brazilian State of Bahia ( Martarega bentoi ), Peru ( Euvelia lata ), and the Peruvian Region of Arequipa ( Microvelia pulchella ).